Manajemen Pendidikan Islam: Leadership dan Administrasi Pendidikan dalam Al-Qur’an - Rubino Rubino; Nuzurul Harmuliani; Sri Wahyuni (Jurnal Dirosah Islamiyah, 2023)
Leadership is a collective effort to solve problems facing the organization through joint thinking and action to achieve well-planned goals. Even though the principal/madrasah is affiliated with an Islamic educational institution, he or she has a leadership role among all members of the school and shares this leadership role and responsibility to achieve a goal. development in an Islamic context urges As a leader, start with those closest to you. Allah says in QS At-Tahrim verse 6 that Allah intends: Remind family members to take care of each other. We are commanded to take care of our families, make sure they do not do what is forbidden to us, and manage our families as God has commanded. Under the protection of 19 leaders, we are trying to save our family from the torments of hell. From the perspective of Islamic education, education management plays an important role in the administration of educational institutions such as schools and madrasas which are based on Islamic values ​​originating from the Al-Quran and As-Sunnah and supported by Islamic educational ideas. Keywords: leadership, education management.